Implementation of the Collaborative Character in Learning Basic Concepts of Plane Figures Through the Kweritop Game - Rifai Zainul Abidin; Agustinus Kevin Jaji; Anis Munfarikhatin (Pendidikan Matematika UNIMOR, 2025)
This research explores the influence of using the traditional game Kweritop on students' collaborative character in understanding the concept of plane figures in mathematics learning at junior high schools in Merauke Regency. This research used an experimental design with two groups: the experimental group that applied the Kweritop game and the control group that used the conventional lecture method. The instrument used is a questionnaire to measure students' cooperative character, which has been tested for validity and reliability. The results of the Mann-Whitney statistical test showed a significant difference between the two groups, where the experimental group showed a higher cooperation rating than the control group. These findings indicate that the Kweritop game can increase student involvement and improve the character of cooperation in mathematics learning so that it can be an effective alternative in local culture-based learning.